Study on demetallization of heavy crude oil using different zeolitic materials - I. M. Othman; Z. F. Ghattas; S. N. Halim; M. A. Elnhal; I. H. Saleh; M. Elsafi (Scientific Reports)
Abstract Refiners downstream worldwide are devoting more attention to managing industrial impacts and environmental contamination as an approach of reducing the trace metal content of heavy crude oil and its refined products. The removal of Cr2+, Ni2+, V4+, and Zn2+ (the most significant metal ions) from Egyptian heavy crude oil at the Belayim Desert (BD) oil field has been studied in this work applying the adsorption demetallization technique. Two types of zeolitic materials have been used in the metal removal experiments. Different operating parameters such as contact time, adsorbent concentration and initial metal ions concentration (crude oil quantity) were investigated for their effects on metal removal efficiency. The experimental results of adsorption test showed that the optimal removal conditions using NZ occurred after 6 h contact time, when using 0.5 g of NZ stirred with 50 ml crude oil, these experimental conditions produced maximum V, Ni, and Cr removal efficiencies as 75.6, 73.9, and 81.8% respectively, that cleared at PXRD and EDX analysis to confirm the highly tendency of NZ to remove metal ions from BD crude oil. While the optimal removal conditions using SZ occurred after 12 h contact time, when using 2 g of SZ stirred with 50 ml crude oil, these experimental conditions produced maximum Zn and Cr removal efficiencies as 70.5, 69.17% respectively, but the maximum removal efficiency of V and Ni obtained after 26 h contact time, 2 g SZ with 50 ml crude oil reached to 68.9%. In addition to the results revealed that Natural Zeolite (NZ) is more efficient than Synthetic Zeolite (SZ) in extracting metal ions mainly Ni and V ions from BD crude oil. Also, the selectivity of NZ for heavy metals removal efficiencies are Cr > V > Ni > Zn. Whilst the selectivity of SZ for heavy metals removal efficiencies are Cr > Zn > V > Ni.